Las Asociaciones Público Privadas como propuesta de solución para la adecuada prestación de los servicios de agua potable y saneamiento en el Perú - Terrones Jancco, Jhojan Cristhian Marquiño (2024)
In the following research, based on the identification of an important gap in the coverage of potable water and sanitation services in Peru, aims to demonstrate that Public Private Partnerships are a proposed solution for the adequate provision of these services. This is due to the fact that this contractual modality allows consolidating opportunities for the development of infrastructure and provision of services in the sanitation sector, looking to i) improve the infrastructure in use, ii) build it in case it does not exist, iii) improve the services provided, and iv) expand the services to the population under conditions of equity, quality, opportunity, continuity and universality.